Cyclosporin A-induced new cementum formation: a morphometric evaluation in the periapical region of rats - Spolidorio, Luis Carlos [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Holzhausen, Marinella [UNESP]; Nassar, Carlos Augusto [UNESP]; Nassar, Patricia Oehlmeyer [UNESP] (FapUNIFESP (SciELO), 2007)
Cyclosporin A (CsA) is a potent immunosuppressor used in organ transplantation and in the management of various autoimmune diseases. Recent studies have shown that CsA stimulates deposition of cementum on root surfaces. The aim of this study was to evaluate the periapical cementum thickness and the apical foramen width in CsA-treated rats. Rats weighing 50 g were treated with a daily injection of 10 mg/kg body weight of CsA in the chow for 60 days. The cementum of the mandibular 1st molars was histologically and morphometricaly examined by analysis of 5-microm-thick serial buccolingual paraffin sections stained with hematoxylin and eosin. Histometric and stereologic analyses revealed the presence of large amounts of cementum in all root surfaces, particularly abundant in the periapical region and obliterating the foramen. The volume density of cementoblasts did not increase. Five to 90 days after the termination of CsA therapy, there was no reduction of cementum thickness. These results suggest that cementum deposition is not reversible after cessation of CsA treatment.

Ciclosporina A (CsA) é um potente imunossupressor usado no transplante de órgãos e no tratamento de várias doenças autoimunes. Recentes estudos têm demonstrado que a CsA estimula a deposição de cemento na superfície radicular. O objetivo deste estudo foi de avaliar a espessura do cemento periapical e largura do forame apical em ratos tratados com CsA. Os ratos pesavam 50 g e foram tratados com doses diárias de 10 mg/kg de peso corporal de CsA no período de 60 dias. O cemento do primeiro molar inferior foi examinado histologicamente e morfometricamente por análises de cortes em parafina com 5µm de espessura no sentido vestíbulo-lingual e corados com hematoxilina e eosina. As análises histométricas e estereológicas revelaram a presença de largos depósitos de cemento em todas as superfícies radiculares, particularmente maior na região periapical e obliterando o forame. A densidade volumétrica dos cementoblastos não foi aumentada. No período de 5 a 90 dias após o término da terapia com CsA, não houve redução na espessura do cemento. Estes resultados sugerem que o depósito de cemento não é reversível após o tratamento com CsA ser cessado.
Keywords: Cyclosporin A; Adverse effects; New cementum formation; Etiology; Animal studies